Ontogenetic approach to grain production in pearl millet (Pennisetum glaucum) based on path-coefficient analysis - YADAV, O P; MANGA, V K; SAXENA, M B L (The Indian Journal of Agricultural Sciences, 2013)
Path-coefficient analyses, based on the ontogeny of pearl millet [Pennisetum glaucum (L.) R. Br. emend. Stuntz] plant, were carried out during rainy seasons (kharif) of 1990 and 1991 to study the relationship among grain yield, yield components. pre-flowering period and threshing ratio. Thirty genotypes weregrown for 2 years at Jodhpur under natural moisture stress during grain-filling stage. Variation in grain yield primarily depended on threshing (%) and panicles/m2. However, 500-grain weight had negligible influence on seed yield. More days to flowering affected adversely the threshing (%), whereas panicles/m2 positively influenced it via pre-flowering period. High threshing ratio increased the 500-grain weight considerably.The variation in panicle length did not significantly influence any trait.